Pengaruh Media Kontras Iopamidol Dosis Tinggi Intravaskuler Terhadap Kadar Kreatinin Serum dan Gambaran Histopatologi Tubulus Ginjal pada Tikus Sprague-Dawley: Upaya Proteksi dengan L-arginin - Hermina Sukmaningtyas; Djoko Untung Trihadi (MEDIA MEDIKA INDONESIANA, 2008)
High dose intravascular iopamidol influence on serum creatinine level and histopatologic feature of kidney tubules in Sprague-Dawley rats: using L-arginine as protectionBackground: Iopamidol, a Low Osmolar Contrast Media (LOCM), has relatively less nephrotoxicity, but contrast media (CM) volume has role to develop acute renal failure even in healthy person. L-arginine as a natural precursor of nitric oxide might prevent contrast nephropathy. Objectives: To investigate effects of iopamidol on acute renal damage by observing serum creatinine level and acute renal necrosis and to assses the role of L-arginine to protect acute renal failure.Methods: This was a post test only control group design experimental study using 35 male, twelve weeks old Sprague-Dawley rats, weighing 200-350 g, allocated into seven groups. The control group (K), P1, P2, P3 were group given 1.8 ml iopamidol and P4, P5, P6 groups were given 8.4% (W/V) L-arginine personde twice a day, 5 ml each for 7 days before 1.8 ml iopamidol injection. Serum creatinine and histological examination were done to assess acute tubular necrosis with H&E staining observed on 24, 48, and 72 hour accordingly. Dose of iopamidol used was equal to 100 ml human dose. The difference of serum creatinine and acute tubular necrosis were analyzed by using ANOVA test.Results: There were no significant differences among groups on serum creatinine level (p=0.261). Acute tubular necrosis increased following iopamidol administration in 72 hour (P3) p=0.007, and pretreatment with L-arginin reduced necrosis in group P6 (p=0.008).Conclusions: Serum creatinine level was not different after administration of iopamidol and L-arginine. Iopamidol induce acute tubular necrosis, while L-arginine can prevent CM-induced nephropathy. Keywords: Iopamidol, serum creatinine, acute tubular necrosis, L-arginine ABSTRAK Latar belakang: Iopamidol, media kontras osmolalitas rendah mempunyai efek nefrotoksik relatif rendah, tetapi pemakaian dosis tinggi merupakan faktor resiko nekrosis tubuler akut. L-arginin, asam amino prekursor NO dan sebagai antioksidan dapat mencegah contrast-induced nephropaty.Tujuan: Mengetahui pengaruh iopamidol terhadap perubahan kadar kreatinin serum dan gambaran nekrosis tubuler akut, serta melihat pengaruh L-arginin terhadap penurunan kejadian contrast-induced nephropaty.Metode: Penelitian eksperimental sesungguhnya dengan rancangan post test only control group design pada tikus Sprague-Dawley jantan, sehat, umur 12 minggu, berat badan 200-350 g. Sebanyak 35 ekor tikus dibagi secara acak menjadi 7 kelompok. Kelompok K, tidak mendapatkan perlakuan, P1, P2, P3 diberi iopamidol 1,8 cc intravena. Kelompok P4, P5, P6 diberi L-arginin 8,4 w/v 2x sehari masing-masing 5 ml selama 7 hari, sebelum disuntik iopamidol 1,8 ml intravena. Kadar kreatinin serum dan pemeriksaan nekrosis tubuler akut diperiksa secara histopatologi dengan pengecatan H&E pada jam ke-24, jam ke-48, jam ke-72 sesuai dengan kelompok perlakuan. Dosis iopamidol setara dengan 100 ml pada dosis manusia. Perubahan kadar kreatinin serum dan nekrosis tubuler akut diuji dengan uji ANOVA.Hasil: Kadar kreatinin serum tidak berbeda di antara kelompok (p=0,261). Pemberian iopamidol menyebabkan nekrosis tubuler akut pada jam ke-72 (p=0,007), dan pemberian L-arginin menurunkan nekrosis tubuler akut pada jam ke-72 (p=0,008). Simpulan: Iopamidol dosis tinggi dapat menginduksi nekrosis tubuler akut pada keadaan tanpa resiko, dan pemberian L-arginin dapat mencegah contrast-induced nephropathy. Kadar kreatinin serum tidak berbeda setelah pemberian iopamidol maupun L-arginin.